Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1155/2021/8085530
|View full text |Cite
|
Sign up to set email alerts
|

Chest CT Findings and Differential Diagnosis of Mycoplasma pneumoniae Pneumonia and Mycoplasma pneumoniae Combined with Streptococcal Pneumonia in Children

Abstract: Background. In this day and age, 17% of children less than 5 years of age died of pneumonia; it is the common cause of children death. It is one of the main children respiratory infectious diseases, i.e., mycoplasma pneumonia (MP). The imaging examination can be adopted to quickly observe the morphology and scope of the pulmonary lesions and know the effect of disease treatment and subsequent changes in the disease in order to provide a basis for treatment. Therefore, the most commonly applied technology for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 43 publications
(42 reference statements)
0
19
0
Order By: Relevance
“…These images are directly visible on a computer monitor in a realistic manner. This enables the doctor to analyze the size, shape, rigidity, and place of doubtful deposits at the same time [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…These images are directly visible on a computer monitor in a realistic manner. This enables the doctor to analyze the size, shape, rigidity, and place of doubtful deposits at the same time [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This paper presents comparative analysis over supervised machine learning (SVM) and graph technique to identify abnormal patient profiles for reliable healthcare data over two healthcare dataset, i.e., Pubmed [ 36 ] and Medhelp [ 37 ]. It determines that the SVM leads over graph-based technique (GBT) and acquires 89%–92% accuracy, whereas SVM gains only 81%–84% accuracy over Pubmed (PM) and Medhelp (MH) dataset, respectively, as shown in Table 6 and Figure 2 .…”
Section: Evaluation Parametermentioning
confidence: 99%
“…Many studies have linked MP infection to asthma attacks. Therefore, MPP is currently considered to be an important cause of asthma exacerbations in nonasthmatic children [ 5 ]. Studies have shown that the abnormal rate of lung imaging of MPP patient is observably higher in contrast to the positive rate of lung signs.…”
Section: Introductionmentioning
confidence: 99%